Regulatory Approaches for Solid Radioactive Waste Storage in Russia - Griffith, A.; Testov, S.; Diaschev, A.; Nazarian, A.; Ustyuzhanin, A. (WM Symposia, Inc., 2003)
The Russian Navy under the Arctic Military Environmental Cooperation (AMEC) Program has designated the Polyarninsky Shipyard as the regional recipient for solid radioactive waste (SRW) pretreatment and storage facilities. Waste storage technologies include containers and lightweight modular storage buildings. The prime focus of this paper is solid radioactive waste storage options based on the AMEC mission and Russian regulatory standards. The storage capability at the Polyarninsky Shipyard in support of Mobile Pretreatment Facility (MPF) operations under the AMEC Program will allow the Russian Navy to accumulate/stage the SRW after treatment at the MPF. It is anticipated that the MPF will operate for 20 years. This paper presents the results of a regulatory analysis performed to support an AMEC program decision on the type of facility to be used for storage of SRW. The objectives the study were to: analyze whether a modular storage building (MSB), referred in the standards as a lightweight building, would comply with the Russian SRW storage building standard, OST 95 10517-95; analyze the Russian SRW storage pad standard OST 95 10516-95; and compare the two standards, OST 95 10517-95 for storage buildings and OST 95 10516-95 for storage pads.